Anti-Freezing multiphase gel materials: Bioinspired design strategies and applications. (June 2020) - Xu, Yichao; Rong, Qinfeng; Zhao, Tianyi; Liu, Mingjie
Highlights: Biochemical and biophysical changes of conifers in cold acclimation and the role of cell wall in the freeze tolerance of conifers were discussed. Two bioinspired strategies for fabrication of anti-freezing gel materials were proposed: (1) suppress the freezing point in a colligative manner, (2) introduce nano-confinement of water molecules between hydrophobic network/moieties to inhibit ice recrystallization and growth. Emerging applications of anti-freezing multiphase gel materials in the energy storage devices including supercapacitors and batteries, sensors, and biocompatibility related applications are summarized. Abstract: Anti-freezing gel materials are an important class of materials that have potential applications in many areas of tissue engineering, soft robots, wearable devices in which ice crystal cannot form or the ice crystal growth is damaging at subzero temperatures. In the increasing need for fabrication of new and innovative anti-freezing soft materials, natural biological systems always provide inspiration and examples that have exceptional hierarchical structural designs and unparalleled performance in freeze-tolerance capabilities. The thoughtful understanding of the freeze-tolerance mechanisms of organisms offers great promise in the synthesis and fabrication of anti-freezing organohydrogels that are difficult to engineer through conventional ideas and approaches. In this review, we propose nature-inspired design principles of anti-freezing gel materials based on the observation of the freeze avoidance/tolerance strategies utilized by various organisms, especially the coniferous trees. Then we detail the pioneering development of anti-freezing multiphase gel material's design and fabrication, and illustrate how these gel materials with unprecedented properties and functionalities can be integrated into devices for various applications under these bioinspired design strategies. Graphical abstract: Image, graphical abstract